Ecological, genetic, and reproductive features of Cenchrus species indicate evolutionary superiority of apomixis under environmental stresses. (October 2019) - Kumar, Suresh; Saxena, Sheena; Rai, Ankita; Radhakrishna, A.; Kaushal, P.
Graphical abstract: Highlights: Cenchrus species possess considerable ecological, reproductive, genetic & molecular diversity. Correlation between apomixis and polyploidy was not exhibited in Cenchrus species. A linkage between apomixis and environmental stress fetches adaptive superiority in plant. Apomixis acts as facilitator of range expansion by rapid propagation of stress-tolerant plant. Apomixis is an adaptation which can be used as ecological indicator of enhanced stress tolerance. Abstract: Many Cenchrus species are resilient to harsh environmental conditions and reproduce through apomixis (asexual seed production), and the resulting progeny is genetically identical to the mother plant. Although the apomictic mode of reproduction restricts the efforts of plant breeders to pyramiding desirable traits, it facilitates the fixation of genetic combinations over multiple generations. Eight Cenchrus species are found in India of which only four apomictic species are grown in sown pastures. We assessed the variability in the morphological, behavioral, ecological, reproductive, genetic and molecular features among the different Cenchrus species, and envisaged a relationship between apomixis and stress tolerance for survival and species propagation under unfavorable ecological conditions. Our findings revealed considerable variability among the Cenchrus species. Molecular diversity analysis grouped the Cenchrus species into two distinct clusters. The apomictic species exhibited a lower diversity than the sexual species. Reproductive pathway diversity (BII and BIII seed formation) among the apomictic Cenchrus species indicated segregation of the components of apomixis, namely parthenogenesis, apomeiosis and functional endosperm formation. For the first time we report partitioning of the components of apomixis in C. glaucus . The earlier reported correlation between apomixis and polyploidy was not observed in the genus Cenchrus . Apomictic Cenchrus species are usually perennial, highly productive and invasive, and adapted to yearly fluctuations in the weather. Sexual Cenchrus species are usually annual, relatively less productive and do not survive during winter. Therefore, we concluded that apomixis facilitates the expansion of species by enabling reproduction even under stressful conditions. The information on genetic and reproductive diversity among the Cenchrus species presented in this study might be useful for interspecific hybridization among these species, as well as to decipher the molecular basis of apomixis in plants.